Synthesis of non-aqueous ionic liquids derived from n-heterocyclic compounds - Shamsuddin, Mustaffa; Mohd. Sirat, Hasnah; Bahari, Zakaria; Ibrahim, Sofian; Ahmad Tajudin, Mohammad Hafiz (Faculty of Science, 2003)
Research in the use of ionic liquid as an alternative solvent for convensional organic solvents in organic synthesis is still in the early stage. In this research, N-methylpyrrolidinium iodide salts have been synthesised from N-methylpyrrolidine with several alkyl iodides. The tetrafluoroborate and hexafluorophosphate salts were synthesised through metathesis reactions with silver tetrafluoroborate and silver hexafluorophosphate respectively. All salts obtained have been characterized using CHN elemental analysis, melting point, density, molar conductivity and 1H-NMR spectroscopy. The melting point range for the N-methylpyrrolidine salts is between room temperature and up to 300Â°C. The correlations between type of anions and alkyl chain length with melting point, density and molar conductivities have been studied. It was found that the length of the alkyl chain has no effect on the melting point of all the iodides, tetrafluoroborates and hexafluorophophates salts. However, the molar conductivities for the salts increase with increasing alkyl chains length and the type or the size of anion. The density of all the salts increase with increasing salts size. This is because salts with bigger size will have a higher density compared with those with smaller size. Room temperature ionic liquids N-methyl-N-propylpyrolidinium tetrafluoroborate (29) and N-butyl-N-methylpyrrolidinium trifluorometanesulfonate (42) has been selected to be used as an alternative for organic solvents in three organic synthesis namely Diels-Alder, Heck and Aldol. In Diels-Alder reactions, the adducts consist of a mixture of exo and endo stereoisomers. The effect of heat towards yield percentage and stereoisomer ratio in the Diels-Alder reactions has been studied. Endo adduct was found to be the main stereoisomer if the reactions were carried out in the presence of heat. In contrast, the exo adduct was the main stereoisomer when the reaction is carried without heat treatment. However, the yield percentages and ratio of exo:endo adducts in ionic liquid solvent are higher than in convensional organic solvents either with or without the presence of heat. In the base catalysed Aldol Condensation reaction, benzaldehyde (59) was reacted with acetone to give dibenzilideneacetone (61), while in the Heck reaction, the ortho, meta and para substituted bromocinnamic acid (58) isomers have been synthesised respectively from the three isomers of bromoiodobenzene (56) and acrylic acid (57). The yield of the products in both the Aldol and Heck reactions are above 80%, which are comparable to the values obtained from similar reactions carried out in conventional organic solvents. Furthermore, the recovery yield of the ionic liquid is sufficiently high, thus render its possibilities for subsequent reactions.